Procedure Of Teaching Grammar Using Memory Enhancement - Susanto, Herri (Bina Nusantara University, 2011)
Teaching grammar has been regarded as a process of understanding from the context. It means a teacher teaches the pupils contextually more than just the rules. However, I have my own experience that teaching grammar methods must depend on the purposes of learning grammar. Some people learn grammar as a means to fulfill the syllabus needs for schools but other people learn grammar for special purposes out of school syllabus, such as for entrance test. For these reasons, the methods of teaching grammar should be different. The students who learn grammar based on the school syllabus probably needs longer procedure of learning that usually uses contextual teaching through listening, speaking, writing, and reading. Nevertheless, students who learn grammar for test need shorter procedure of learning such as memorizing. Therefore, I propose giving a workshop of teaching grammar using memory enhancement as another alternative teaching grammar method. This workshop would show the class that grammar can be learnt through memory enhancement process, i.e.; mind map, music, memory technique and drill to boost up students understanding for test preparation.